2019
DOI: 10.1136/bmj.l1927
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care use and mortality among patients with ST elevation myocardial infarction: retrospective cohort study

Abstract: ObjectiveTo evaluate the effect of intensive care unit (ICU) admission on mortality among patients with ST elevation myocardial infarction (STEMI).DesignRetrospective cohort study.Setting1727 acute care hospitals in the United States.ParticipantsMedicare beneficiaries (aged 65 years or older) admitted with STEMI to either an ICU or a non-ICU unit (general/telemetry ward or intermediate care) between January 2014 and October 2015.Main outcome measure30 day mortality. An instrumental variable analysis was done t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…IV analysis can adjust for both measured and unmeasured confounders when an appropriate IV is used. Differential distance was used as an IV, as in a previous study that determined the effect of using the ICU to reduce mortality associated with myocardial infarction. The differential distance was defined as the difference between the distance from a patient's residence to the nearest hospital where colectomies were performed in a year and the distance from a patient's residence to the nearest hospital where colonic stent insertions were performed in the year.…”
Section: Methodsmentioning
confidence: 99%
“…IV analysis can adjust for both measured and unmeasured confounders when an appropriate IV is used. Differential distance was used as an IV, as in a previous study that determined the effect of using the ICU to reduce mortality associated with myocardial infarction. The differential distance was defined as the difference between the distance from a patient's residence to the nearest hospital where colectomies were performed in a year and the distance from a patient's residence to the nearest hospital where colonic stent insertions were performed in the year.…”
Section: Methodsmentioning
confidence: 99%
“…Two previous studies reported no impact of CCU use on clinical outcomes in patients with NSTEMI with low in-hospital mortality (1.3% vs. 1.2% in the CCU and GW groups) and STEMI patients with low APACHE III scores and a low likelihood of complications [15,16]. On the other hand, Valley et al showed that ICU admission was associated with improved survival at 30 days among patients with STEMI with high mortality (14.3% vs. 8.3% in the ICU and GW groups) [14]. This may explain the survival benefit of the ICU in high-risk cohorts, whereas low-risk patients (i.e., patients with low in-hospital mortality) may be managed appropriately in the GW.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, we examined the length of stay and total hospitalization costs. The total duration of hospitalization was shorter (11 [9][10][11][12][13][14][15] vs. 12 [9][10][11][12][13][14][15][16] days, p<0.001), and total hospitalization cost was lower in the GW group than in the CCU group after PSM (1780000 [1480000-2150000] vs. 1830000 [1560000-2240000] JPY, p<0.001)…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Valley et al identified patients without clear indication for the ICU and demonstrated an absolute mortality reduction of 6% in those patients admitted to the ICU on a discretionary basis. 9 Cardiac arrest is the most feared complication of STEMI, as it is the primary cause of short-term STEMI-associated mortality occurring in 5 À10% of STEMI patients. 3,4 The majority of these cardiac arrests are out-of-hospital.…”
mentioning
confidence: 99%